2020
DOI: 10.21608/mid.2020.37760.1045
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of Moringa Oleifera methanolic leaves extracts against some Gram positive and Gram negative bacterial isolates

Abstract: Background: Moringa oleifera Lam. (Moringaceae) found to be very useful tree in tropical countries. In folklore and Ayurvedic all parts of the tree are used in different healing procedures for different diseases. The plant leaves are very good nutrient supplement for malnutrition and also used as an antibiotic. Methods: Phytochemical analysis of the leaf in solvents of varying polarity; viz., aqueous and methanol were also carried out. Results: The phytochemical screening indicated the presence of phenolics, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
2
4
0
Order By: Relevance
“…These results are consistent with the recent report, which demonstrated that aqueous solvents produce extracts higher than methanol solvents [ 39 ]. Other researchers reported that extracting M. oleifera leaves (1.5 g) with different polarity solvents resulted in dry extracts with a weight of 5%–36% ( M. oleifera leaf hexane extract) [ 26 ].…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…These results are consistent with the recent report, which demonstrated that aqueous solvents produce extracts higher than methanol solvents [ 39 ]. Other researchers reported that extracting M. oleifera leaves (1.5 g) with different polarity solvents resulted in dry extracts with a weight of 5%–36% ( M. oleifera leaf hexane extract) [ 26 ].…”
Section: Resultssupporting
confidence: 94%
“…Bacterial growth inhibition based on extract concentrations implies that increasing the concentration of the methanol extract increases inhibitory absorption. These findings support previous research that M. oleifera leaf powder has antibacterial activity against negative bacteria at a low level [ 39 ]. Kumar et al [ 45 ] reported that the M. oleifera extract with the dilution method has an antibacterial activity with a minimum inhibitory concentration of 7.4 mg/mL and 2.4 mg/mL for S. aureus and E. coli , respectively.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Broad-spectrum antibacterial efficacy of the M. oleifera plant was confirmed also against most pathogenic Gram-positive and Gram-negative organisms in many reports in which greater inhibition zones of Moringa were recorded against S. aureus and E. coli isolates ( Abd El-Moez et al ., 2014 ). In addition, recent reviews declared that the ethanol and methanol extracts of M. oleifera could suppress the viability of Salmonella typhi , Salmonella paratyphi , E. coli, B. cereus , Shigella, S. aureus , and E. faecalis organisms (Híjar et al ., 2018; Salihu Abdallah et al ., 2019 ; Abdallah et al ., 2022 ; Adji et al ., 2022 ) than the aqueous extract. The active components responsible for the bactericidal activity are more soluble in organic solvents than water extract ( Prabakaran et al ., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 42 ] To date, many studies have been done to assess the antimicrobial effectiveness of M. oleifera . [ 43 ] The evaluated results showed that the M. oleifera leaves extract showed anti-bacterial properties against both Gram-positive and Gram-negative bacteria, however, it exhibited more potent antimicrobial activity against Gram-negative bacteria than Gram-positive strains. [ 43 ]…”
Section: Discussionmentioning
confidence: 99%